Quality by Design (QbD) Approach to Develop Colon-Specific Ketoprofen Hot-Melt Extruded Pellets: Impact of Eudragit® S 100 Coating on the In Vitro Drug Release - Sateesh Kumar Vemula; Sagar Narala; Prateek Uttreja; Nagarjuna Narala; Bhaskar Daravath; Chamundeswara Srinivasa Akash Kalla; Srikanth Baisa; Siva Ram Munnangi; Naveen Chella; Michael A. Repka (MDPI AG, 2024)
Background: A pelletizer paired with hot-melt extrusion technology (HME) was used to develop colon-targeted pellets for ketoprofen (KTP). Thermal stability and side effects in the upper gastrointestinal tract made ketoprofen more suitable for this work. Methods: The pellets were prepared using the enzyme-triggered polymer Pectin LM in the presence of HPMC HME 4M, followed by pH-dependent Eudragit® S 100 coating to accommodate the maximum drug release in the colon by minimizing drug release in the upper gastrointestinal tract (GIT). Box-Behnken Design (BBD) was used for response surface optimization of the proportion of different independent variables like Pectin LM (A), HPMC HME 4M (B), and Eudragit® S 100 (C) required to lower the early drug release in upper GIT and to extend the drug release in the colon. Results: Solid-state characterization studies revealed that ketoprofen was present in a solid solution state in the hot-melt extruded polymer matrix. The desired responses of the prepared optimized KTP pellets obtained by considering the designed space showed 1.20% drug release in 2 h, 3.73% in the first 5 h of the lag period with the help of Eudragit® S 100 coating, and 93.96% in extended release up to 24 h in the colonic region. Conclusions: Hence, developing Eudragit-coated hot-melt extruded pellets could be a significant method for achieving the colon-specific release of ketoprofen.